Effect of Fe/Ta doping on structural, dielectric, and electrical properties of Bi4Ti2.5Fe0.25Ta0.25O12 ceramics. Issue 2 (11th October 2016) - Rehman, Fida; Wang, Lin; Jin, Hai‐Bo; Bukhtiar, Arfan; Zhang, Ruibo; Zhao, Yongjie; Li, Jing‐Bo
Abstract: Aurivillius single‐phase Bi4 Ti2.5 Fe0.25 Ta0.25 O12 ceramics was prepared via high‐temperature solid‐state reaction method. The detailed structural analysis of the doped Bi4 Ti3 O12 compound was carried out by Rietveld refinement of the full XRD Pattern. Dielectric and electrical properties were studied in a wide range of temperature and frequency by dielectric/impedance spectroscopies. The comprehensive analysis of frequency spectrum reveals the occurrence of two relaxation behaviors in the ceramics at low frequency and high frequency, respectively. A phase transition was observed at ~650°C in Bi4 Ti2.5 Fe0.25 Ta0.25 O12 somewhat lower than the ferroelectric transition temperature of Bi4 Ti3 O12 . The possible reason for the decrease of ferroelectric transition temperature was discussed based on the structural analysis. The present results could be useful for designing and/or modifying properties of Bi4 Ti3 O12 ‐related ceramics.